2017
DOI: 10.1542/hpeds.2016-0104
|View full text |Cite
|
Sign up to set email alerts
|

Care Variations and Outcomes for Children Hospitalized With Bacterial Tracheostomy-Associated Respiratory Infections

Abstract: Objective Identify hospital-level care variations and association with length of stay (LOS) and hospital revisit in children with tracheostomies hospitalized for bacterial respiratory tract infections (bRTI). Method Multicenter retrospective cohort study using the Pediatric Health Information System database between 2007–2014 of patients with tracheostomies aged ≤18 years with a primary diagnosis of bRTI (e.g. tracheitis) or a primary diagnosis of bRTI symptom (e.g. cough) and secondary diagnosis of bRTI. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 25 publications
0
46
0
5
Order By: Relevance
“…To define our outcome of interest, we only labeled follow-up visits as due to a bRTI if they had appropriate ICD-9-CM codes and treatment with antibiotics used in previous studies. [11][12][13][14][15][16] Unfortunately, PHIS does not provide any microbiology testing results and we are unable to detect bacterial culture or gram stain results, limiting our ability to assess for acute infection versus chronic colonization. We also recognize the possibility that our study may have misclassified some patients with viral respiratory infections as having bacterial respiratory tract infections.…”
Section: Clinical Comorbidities and Brti Hospital Readmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…To define our outcome of interest, we only labeled follow-up visits as due to a bRTI if they had appropriate ICD-9-CM codes and treatment with antibiotics used in previous studies. [11][12][13][14][15][16] Unfortunately, PHIS does not provide any microbiology testing results and we are unable to detect bacterial culture or gram stain results, limiting our ability to assess for acute infection versus chronic colonization. We also recognize the possibility that our study may have misclassified some patients with viral respiratory infections as having bacterial respiratory tract infections.…”
Section: Clinical Comorbidities and Brti Hospital Readmissionmentioning
confidence: 99%
“…This was to minimize including patients that underwent decannulation at a non-PHIS hospital and who were readmitted for a bRTI but did not have a current tracheostomy in place. bRTI were identified by modifying strategies based upon previous PHIS work in ICD-9-CM codes for bacterial pneumonia and aspiration pneumonia; [11][12][13][14][15][16] given the patient population, we also added acute tracheitis (464.1x) codes.…”
mentioning
confidence: 99%
“…Of these hospitalizations, bacterial pneumonia is the most common ambulatory care sensitive condition (conditions for which appropriate ambulatory care prevents or reduces admission to the hospital) requiring hospitalization . Previous research has shown that the wide diagnostic and therapeutic variations of pediatric patients hospitalized with bacterial tracheostomy‐associated respiratory tract infections (bTARTIs) are not associated with length of stay (LOS) or readmission . Because children with tracheostomy account for high utilization of health care resources, identification of high‐risk subpopulations, and modifiable factors may assist in development of evidence‐based best practices for the prevention and treatment of these infections, and decrease hospital admissions and healthcare expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for frequent pneumonia hospitalizations is that up to 90% of pediatric patients with tracheostomy have respiratory cultures positive for Pseudomonas aeruginosa ( P. aeruginosa ), a multidrug resistant bacterium with limited oral treatment options, at some point post‐tracheotomy . Indeed, over 70% of pediatric patients hospitalized bTARTIs receive empiric antibiotics that target P. aeruginosa ) . While previous literature in patients with cystic fibrosis (CF) demonstrated associations between P. aeruginosa acquisition and both increased CF exacerbation rates, and declining pulmonary status and greater mortality, the relationship between P. aeruginosa and outcomes in pediatric patients with tracheostomy remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation